Identifying the activity – based hazards involved in the terralink construction method - Mohd Kabri, Muhamad Afiq Al-Amin; Mohd Kamar, Izatul Farrita; Husin @ Husain, Husrul Nizam; Putra Utama, Wahyudi (UiTM Press, 2025)
A major geologic hazard that occurs frequently throughout the world is landslides. Slope failures and landslides are common in Malaysia, despite the country's lack of precipitation (less than 25% of the area is made up of hills and mountains). Each year, landslides will result in thousands of fatalities and injuries and billions of ringgits in property damage. In Malaysia, the terralink construction method was the new method used for the slope repair project at Simpang Pulai-Blue Valley Road. However, there is no existing risk management plan for the terralink construction method. Hence, there is a need to identify the activity-based hazards involved in this method. The study utilised a qualitative approach and was conducted via the interview method. The interview was conducted at three agencies, each represented by JKR, a consulting firm and the main contractor. It was found that six categories of hazards occur when using the terralink construction method, such as safety, natural disaster, schedule, scope, environment, and technical. Activity-based hazards were found in the above categories. This study intends to contribute to producing information and data regarding the Risk Management Plan to all stakeholders as future references.